Structural analysis : in theory and practice - Williams, Alan, 1930- (Elsevier/Butterworth-Heinemann ; International Code Council, 2009)
Structural Analysis Rules of Thumb provides a comprehensive review of the classical methods of structural analysis and also the recent advances in computer applications. The prefect guide for the Professional Engineer's exam, Williams covers principles of structural analysis to advanced concepts. Methods of analysis are presented in a concise and direct manner and the different methods of approach to a problem are illustrated by specific examples. In addition, the book include the clear and concise approach to the subject and the focus on the most direct solution to a problem. Numerous worked examples are provided to consolidate the readers? understanding of the topics. Structural Analysis Rules of Thumb is perfect for anyone who wishes to have handy reference filled with equations, calculations and modeling instructions as well as candidates studying for professional engineering registration examinations. It will also serve as a refresher course and reference manual for practicing engineers. Registered professional engineers and registered structural Numerous worked examples are provided to consolidate the readers? understanding of the topics Comprehensive coverage of the whole field of structural analysis Supplementary problems are given at the end of each chapter with answers provided at the end of the book Realistic situations encountered in practice and test the reader's ability to apply the concepts presented in the chapter Classical methods of structural analysis and also the recent advances in computer applications.